A THEORETICAL STUDY OF PREDICATE EXPRESSION IN UZBEK (Web of Teachers: Inderscience Research, 2026)
This article explores the syntactic and morphological mechanisms involved in the formation of predicates in the Uzbek language. It provides a theoretical analysis distinguishing between verbal and non-verbal predicates, focusing on the roles of head movement and Local Dislocation in predicate expression. Drawing on recent linguistic research and syntactic theory, the paper explains how verbs, nouns, adjectives, and participles function as predicates in Uzbek sentence structures. With detailed examples and references to contemporary linguistic theory, this study contributes to our understanding of predicate syntax in Turkic languages and broader typological patterns in morphosyntax.